Penerapan Pembelajaran Tematik Model Webbed untuk Meningkatkan Motivasi Siswa Kelas II SD Inpres Sopi - Jenni Rombe; M. Rais Salim; Amrin Sibua (Jurnal Ilmiah Wahana Pendidikan, 2020)
Research conducted by researchers is using a qualitative research approach with descriptive qualitative types. Methods of data collection by observation, interviews and documentation. The implementation of thematic learning consists of opening activities, core activities consisting of exploration, elaboration, confirmation. And the last activity is the closing activity. The implementation of thematic learning on the spider web model (webbed model) consists of several indicators from several subjects which are combined into one theme in each meeting. Assessment in thematic learning is carried out separately in each subject indicator. Assessment in thematic learning does not only look at the results but also the learning process. Assessment tools that can be used in thematic learning include written tests, oral tests, action tests, and portfolios